Use of levodopa-carbidopa intestinal gel to treat patients with multiple system atrophy. (July 2022) - Blaise, A.S.; Cuvelier, E.; Carrière, N.; Devos, D.; Moreau, F.; Defebvre, L.; Mutez, E.
Abstract: Background: Levodopa-carbidopa intestinal gel (LCIG) is an effective treatment for late-stage Parkinson's disease (PD) but had not been evaluated in levodopa-responsive patients with the parkinsonian variant of multiple system atrophy (MSA-P) and motor fluctuations. We aimed to assess the safety of LCIG in MSA-P patients. Methods: In a retrospective, single-center study, we analyzed clinical and treatment-related data for all patients with MSA-P or PD treated with LCIG between December 2004 and November 2017. Adverse events (AEs) were classified into three classes: AEs related to gastrointestinal effects or to the PEG-J procedure, AEs related to the device, and AEs related to the pharmacological effect of LCIG. Results: 7 MSA-P and 63 PD patients had been treated with LCIG for a median [interquartile range] period of 31 [16;43] and 19 [8;45] months, respectively. There were no significant intergroup differences in safety. Enteral nutrition was introduced at the same time as LCIG treatment in 4 (57%) MSA-P patients. In the MSA-P and PD groups, LCIG was associated with a better Global Clinical Impression score and discontinuation of oral anti-parkinsonian drugs (in 43% and 27% of cases, respectively). Conclusions: LCIG treatment is feasible in MSA-P patients with severe motor complications. The safety profile is similar to that seen in PD. Highlights: One third of MSA-P patients show a levodopa-responsiveness. LCIG may be used in levodopa-responsive patients with MSA-P. The safety profile of LCIG treatment in MSA-P appears to be similar to that in PD.